Problematika Guru Bahasa Inggris dalam Pelaksanaan Pembelajaran Berbasis Teknologi Informasi dan Komunikasi - Ratna Dewi; Rita Erlinda; Muhammad Fazis; Annisaul Khairat (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Currently it is very necessary and important to use Information and Communication Technology (ICT) in learning activities, especially by teachers during the learning process, but teachers still find it difficult and have problems in managing learning using ICT. So the purpose of this study was to find out the problems of teachers in implementing ICT-based learning in English subjects at MTsN Tanah Datar District. This type of research is phenomenology with a qualitative approach. The research locations were at MTsN Tanah Datar District, namely MTsN 1 Tanah Datar, MTsN 3 Tanah Datar, MTsN 6 Tanah Datar, MTsN 10 Tanah Datar, MTsN 12 Tanah Datar and MTsN 17 Tanah Datar. Informants in this study were English teachers at MTsN Tanah Datar District. The instrument in this study was an interview guide. Data collection techniques in this study were semi-structured interviews. The results showed that the teacher's problems in implementation were limited internet access/network, limited facilities/means, spending time preparing tools/means, not achieving learning targets.